The scandal of Pentecost: a theology of the public church - Vondey, Wolfgang (T&T Clark, 2025)
"Through a systematic analysis of the conflicts emerging when the public church encounters the public world, The scandal of Pentecost argues that the public advent of the church stands in continuity with the public scandal of the incarnate and crucified Christ. The book traces the contours of this scandal in the confrontation of the dominant ruling hermeneutic of resistance. This highlights the brokenness of the human conditon manifested by the church in the drunkenness of the disciples, the speaking in other tongues, the baptism with the Spirit, the empowerment of the flesh and its public witness to a scandalixed world." --